Air leakage levels in timber frame building envelope joints. (1st May 2017) - Kalamees, Targo; Alev, Üllar; Pärnalaas, Mihkel
Abstract: Air leakage levels from eight joints that use different tightening solutions for a prefabricated timber frame building envelope were measured under laboratory conditions. Air tightness levels in field conditions were also studied by using houses that have already been built. Joints in the external wall with an inserted floor and separating walls, as well as in the external corner of walls, all showed the largest levels of air leakage. The lowest air leakage levels were recorded in the joint between the external wall and the window. Tightening up the external weather barrier significantly improved the air tightness levels of the joints. Using self-adhesive tape in tightening up the air-vapour barrier and the weathering barrier seems to be the most promising solution when it comes to guaranteeing the air tightness of wooden-framed structures. The difference between air leakage levels as measured in field conditions and those which were calculated based on laboratory measurements was noticeably large. This was caused mainly by workmanship quality levels on the construction site sealing the building envelope's joints and the fact that there were other leakage places in addition to the typical joints that were studied. Improved research, development, design, construction, and supervision are needed to fulfil airtightness requirements in future construction when it comes to producing nearly Zero Energy Buildings (nZEB). In order to be able to estimate the airtightness levels of a building in the design phase a larger database is needed, with different combinations made available in terms of joints, materials, and workmanship. Highlights: An experimental study on the airtightness of timber-framed building envelope joints. The largest leakage was in joints in which the air-vapour barrier is discontinued. Self-adhesive tape seems to be the most promising tightening solution. Workmanship quality levels plays a critical role in achieving airtightness.